Transforming Swamp Buffaloes to Producers of Milk and Meat Through Crossbreeding and Backcrossing - Cruz, L C (Indonesian Animal Sciences Society, 2009)
There are two major types of water buffaloes in the world, the riverine type and the swamp type. The total number of Swamp buffalo is 37.6 M and represents 21.8% of the worldâs buffalo population. The swamp buffaloes have played a major role in draft animal-dependent farming system. But intensified rice production became more pronounced in irrigated areas and this has led to increased utilization of small farm machineries, displacing significantly the draft buffaloes for land tillage. To some extent, the introduction of tractors for land preparation and transport for corn, sugarcane and other crops in production areas has similar effect. Utilization of the existing population of swamp buffaloes to meet the growing domestic demand for milk and meat, against the background of increasing farm mechanization, is a good reason to transform the huge number of draft animals into producers of milk and meat. According to the UNDP/FAO-assisted project in the Philippines carried from 1982 to 1998, that crossing swamp buffalo and riverine buffaloes, despite the differences in chromosome numbers, is producing crossbreds with high growth rate potentials and milk production abilities several folds over the swamp buffalo parents. The known fact that swamp and riverine buffaloes have different chromosome number, the diploid chromosome number of the swamp buffalo is 48 and that of the river buffalo is 50. When crossbreeding between the 2 buffalo types occur, males and females of the F1 generation are heterozygous for the fusion and are apparently fertile with chromosome 2n = 49. Three-way crossbred hybrids were obtained by (native buffalo x Murrah x Nili Ravi) or (native buffalo x Nili Ravi x Murrah). They had two chromosome categories viz. 2n=49 and 2n=50, respectively. Crossbreeding Swamp with Riverine Breed is done for quality beef. Most of the NT produced TenderBuff is farm-bred or purchased from other suppliers as swamp buffalo yearlings and growth out for a further 8 â 16 months to achieve target weights on the pastures. The reproductive performance of F1 females produced out of crossing Murrah buffalo and Philippine carabao are not different. Assessment of the fertility of F1 bulls was made on the basis of the pregnancy rate obtained from AI on Philippine carabaos using frozen semen. The data indicated that there was no significant difference between the pregnancy rate of the Philippine carabaos inseminated with either Murrah buffaloes or F1 frozen semen. However, a signigicant difference on conception rate was observed (P < 0.05) compared to hybrid with 2n = 50 chromosomes. The calving rate of hybrids with 2n = 49 chromosomes decreased by 17.77 â 17.89% and the total calves reduced by 1.33 â 1.54 heads from the first calving to age of 11 years. The fundamental initiative that is most consistent with the envisaged improvement in the productivity of the carabao is the establishment of germplasm pools from where superior materials can be obtained on a sustainable basis such as Gene Pools for Selected Native Philippine Carabao (PC), Gene Pool for Riverine Buffalo for Meat Improvement, Gene Pool for Improvement for Milk Production. From the above point of view, the future will see sustained and more intensive efforts to pursue the goal of transforming genetically the traditionally draft animal to producer of milk and meat and eventually establishment of viable and progressive buffalo-based enterprises.Â Key words: Swamp buffalo, crossbreeding, backcrossing